Revision of genus Stilbotes Stål (Hemiptera: Pentatomoidea: Pentatomidae: Asopinae) with description of a new species - Roca-Cusachs, Marcos; Kim, Junggon; Lee, Hodan; Lee, Gwan-Seok; Jung, Sunghoon (Zootaxa, 2018)
The Asopinae genus Stilbotes Stål, 1871 from Philippines is reviewed taxonomically. A new species Stilbotes goulae sp. nov. is described based on female specimens. Stilbotes semperi Stål 1871 is redescribed in detail. A diagnosis, key and distributional records for the genus and the species are also provided.